2013
DOI: 10.3350/cmh.2013.19.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and epidemiological characteristics of Korean patients with hepatitis C virus genotype 6

Abstract: Background/AimsThe distribution of hepatitis C virus (HCV) genotypes varies geographically. In Korea, genotypes 1 and 2 comprise more than 90% of HCV infections, while genotype 6 is very rare. This study compared the clinical and epidemiological characteristics of patients with genotype 6 HCV infection with those infected with HCV genotypes 1 and 2.MethodsThis was a prospective, multicenter HCV cohort study that enrolled 1,173 adult patients, of which 930 underwent HCV genotype analysis, and only 9 (1.0%) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Eight studies were identified as redundant and excluded: duplicates found during our search or earlier abstracts of full articles that were later published [15,19,30–33,42,43]. Six studies included less than ten HCV-6 patients [3436,44–46]. Four studies did not include patients treated with PEG IFN+RBV [3740].…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies were identified as redundant and excluded: duplicates found during our search or earlier abstracts of full articles that were later published [15,19,30–33,42,43]. Six studies included less than ten HCV-6 patients [3436,44–46]. Four studies did not include patients treated with PEG IFN+RBV [3740].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, between 2013 and 2015, HCV genotype 2a showed a marked increase in Cheonan area. Furthermore, genotype 1b showed an increase, particularly in 2010, compared with the findings of other studies in Korea [2,13,14]. Thus, it was concluded that these genotypes were endemic during these years.…”
Section: Discussionmentioning
confidence: 43%
“…Furthermore, HCV infection was identified in 10% of patients with hepatocellular carcinoma (HCC) in Korea in 2010s [9], with HCV genotype 1b associated with a higher risk of HCC than genotypes 2a, 2c, or other genotypes worldwide [10−12]. In Korea, the most frequently detected genotypes are genotypes 1b and 2a; however, the related studies are limited [2,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In Hong Kong, HCV GT6 was pre‐dominantly encountered in PWIDs (range 58.5%‐62.5%) and in 50% of those with thalassemia major . Similarly, GT6 infection appeared to be increasingly common among in PWID in Myanmar, Southern China (41%), Taiwan (27%‐28%) and Korea as compared to non‐PWID HCV‐infected population . Apart from Southeast and East Asia, HCV GT6 infections have also been reported in other parts of the world, mainly among immigrants from Asia.…”
Section: Epidemiologymentioning
confidence: 99%